The Power of Patristic Preaching : The Word in Our Flesh - Hofer, Andrew (Book collections on Project MUSE., 2023)
"A remarkable retrieval of the spirit of patristic preaching, this book will be valuable for students and scholars of the Church Fathers, a vital resource for preachers, and of interest to all those seeking to deepen their knowledge and experience of Christian worship." [from back cover "Very Reverend Archimandrite Maximos Constas"]